Fiscal Risks : Sources, Disclosure, and Management - Lusinyan, Lusine (Departmental Papers; Departmental Paper ;, 2009)
This paper analyzes the main sources of fiscal risks, including from unexpected changes in macroeconomic variables and banking crises, which can have major consequences for countries fiscal and public debt sustainability. It builds on an overview of existing practices in a wide range of countries to provide practical suggestions on how to promote disclosure of such risks and on risk mitigation and management. The paper was written in response to requests from IMF member countries for advice on this subject. The paper also includes an example of a possible statement of fiscal risks.